Increasing Public Sector Revenue in the Philippines : Equity and Efficiency Considerations - Fletcher, Kevin (IMF Working Papers; Working Paper ;, 2005)
Public sector revenue has declined markedly in the Philippines over the past seven years. Most observers of the Philippine economy agree that rebuilding public sector revenue will be critical to reducing deficits and ensuring public sector debt sustainability. This paper reviews several of the main possibilities for raising public sector revenue, including increases in excise, VAT, and electricity rates. It argues that most of these proposals would raise revenue in a relatively efficient manner. Using household-level expenditure data, it also finds that most of these measures would be progressive, especially if they allow the government to avoid cuts in pro-poor spending.